Colloidal liquid crystal type assemblies of spheroidal polystyrene core/polyglycidol‐rich shell particles (P[S/PGL]) formed at the liquid‐silicon‐air interface by a directed dewetting process. (17th April 2019) - Mickiewicz, Damian; Basinska, Teresa; Gosecka, Monika; Gadzinowski, Mariusz; Slomkowski, Stanislaw
Abstract : A method for the preparation of stripe‐like monolayers of microspheroids is described. The particles were obtained from polystyrene core/polyglycidol‐rich shell microspheres by stretching poly (vinyl alcohol) films that contain embedded particles. The stretching was performed under controlled conditions at temperatures above the Tg of the films and particles. The elongated films were dissolved in water, and the microspheroids were subsequently removed and purified from the poly (vinyl alcohol). The aspect ratio (AR) of the particles, which denotes the ratio of the lengths of the longer to shorter particle axes, was determined by the film elongation. The AR values were in the range of 2.9‐7.7. Spheroidal particles with various ARs were deposited onto silicon wafers from an ethanol (EtOH) suspension. The particle concentration and volume of the suspension were the same in each experiment. Evaporation of the EtOH yielded stripes of spherical particles packed into nematic‐type colloidal crystals and assembled into monolayers. The orientation of the stripes after ethanol evaporation was perpendicular to the triphasic (silicon‐ethanol‐air) interface along the silicon substrate. The adsorbed stripes on the wafers were characterized in terms of their interstripe distance (ID), stripe width, and crystal domain size. Nematic‐type spheroid arrangements in the stripes were the dominant structure, which enabled denser packing of the particles into colloidal crystals than that allowed by the smectic‐type arrangements. Furthermore, the number of spheroids adsorbed per surface unit of the silicon wafers was similar for all ARs, but the width and frequency of the spheroid stripes adsorbed on the wafers were different.